Double Laplace-Sawi Transform (European Journal of Pure and Applied Mathematics, 2025)
The primary objective of this study is to develop a new integral transform by combining the Laplace and Sawi transforms, and to investigate its key properties, existence, and the inversion theorem. Furthermore, we introduce new results related to partial differential equations in higher dimensions and extend the double convolution theorem to two dimensions. Using these new properties and theorems, we solve special type differential equations with some real applications in physics and related sciences.
Keywords: Double integral transform; Laplace-Sawi transform; Laplace transform; Sawi transform